The Between-Population Genetic Architecture of Growth, Maturation, and Plasticity in Atlantic Salmon. Issue 4 (1st April 2014) - Debes, Paul Vincent; Fraser, Dylan John; Yates, Matthew; Hutchings, Jeffrey A
Abstract: The between-population genetic architecture for growth and maturation has not been examined in detail for many animal species despite its central importance in understanding hybrid fitness. We studied the genetic architecture of population divergence in: (i) maturation probabilities at the same age; (ii) size at age and growth, while accounting for maturity status and sex; and (iii) growth plasticity in response to environmental factors, using divergent wild and domesticated Atlantic salmon ( Salmo salar ). Our work examined two populations and their multigenerational hybrids in a common experimental arrangement in which salinity and quantity of suspended sediments were manipulated to mimic naturally occurring environmental variation. Average specific growth rates across environments differed among crosses, maturity groups, and cross-by-maturity groups, but a growth-rate reduction in the presence of suspended sediments was equal for all groups. Our results revealed both additive and nonadditive outbreeding effects for size at age and for growth rates that differed with life stage, as well as the presence of different sex- and size-specific maturation probabilities between populations. The major implication of our work is that estimates of the genetic architecture of growth and maturation can be biased if one does not simultaneously account for temporal changes in growth and for different maturation probabilities between populations. Namely, these correlated traits interact differently within each population and between sexes and among generations, due to nonadditive effects and a level of independence in the genetic control for traits. Our results emphasize the challenges to investigating and predicting phenotypic changes resulting from between-population outbreeding.